2012
DOI: 10.1186/1471-2393-12-84
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unwanted pregnancies in India using matched case-control designs

Abstract: BackgroundIn India, while the total fertility rate has been declined from 3.39 in 1992–93 to 2.68 in 2005–06, the prevalence of unintended pregnancy is still stagnant over the same period. A review of existing literature shows that within the country, there are variations in fertility preferences between different regions. Also there is a strong argument that the availability of a health facility at the village level plays an important role in reshaping the fertility behavior of women. Keeping in mind the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 32 publications
8
50
1
Order By: Relevance
“…Gender, religion, domicile, education status and socioeconomic status have significant impact on unwanted pregnancy and use of contraception. 7 In the present study, only academic year showed significant difference in knowledge. For obvious reason, final year students and interns have more knowledge than first and second year students.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Gender, religion, domicile, education status and socioeconomic status have significant impact on unwanted pregnancy and use of contraception. 7 In the present study, only academic year showed significant difference in knowledge. For obvious reason, final year students and interns have more knowledge than first and second year students.…”
Section: Discussionmentioning
confidence: 66%
“…7 EC helps in preventing pregnancy when routine contraception fails and unprotected intercourse happens. ECPs are effective within 72 hours after intercourse, but recent studies have confirmed that they are effective for up to 120 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher rates of unwanted pregnancies in urban areas were reported among HIV uninfected women in India (Dixit et al, 2012) but not elsewhere (Kassa et al, 2012;Wado, Afework, & Hindin, 2013) suggesting similarity in the vulnerabilities and constraints among Indian urban women irrespective of their HIV status.…”
Section: Analysis Of First Pregnancy After Hiv Diagnosis (N=113)mentioning
confidence: 85%
“…Higher parity has been consistently reported as a significant predictor of unwanted pregnancies among HIV infected (Bankole et al, 2014;Liang et al, 2013) and uninfected women (Dixit, Ram, & Dwivedi, 2012;Ikamari, Izugbara, & Ochako, 2013;Kassa, Berhane, & Worku, 2012).…”
Section: Analysis Of First Pregnancy After Hiv Diagnosis (N=113)mentioning
confidence: 97%
“…1 Every fourth pregnancy in India resulting in live birth is mistimed or unplanned 1 . Despite the 'cafeteria approach' of Reproductive and Child Health programme in India with the availability of a range of contraceptives to suit the different requirements of different couples, numbers of unwanted pregnancies is still very high.…”
Section: Introductionmentioning
confidence: 99%